Construction of five novel coordination polymers based on maloyl-bis-2-aminobenzothiazole: synthesis, structural, thermal, and non-isothermal kinetics. Issue 2 (3rd April 2017) - Padole-Gaikwad, Geeta S.; Bagade, Rina D.; Chaudhary, Ratiram Gomaji; Gharpure, Mangesh P.; Juneja, H. D.
Abstract :